Sintesa Precipitated Calcium Carbonate (PCC) Dari Kulit Kerang Darah (Anadara Granosa Dengan Variasi Konsentrasi Asam Dan Rasio CaO/HNO3 - Dhini Octavianty; Amun Amri; Zultiniar Zultiniar; Yelmida Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The purpose of this research was production of precipitated calcium carbonate (PCC) from blood cockle shell waste using carbonation method. Carbonation method that was used to synthesis PCC was modificated carbonation method by CaO as calcination result and HNO3 reaction and then flowed the CO2 gas. The learned variable was variation of the nitric acid concentration (1,5; 2; and 2,5 M) and CaO/HNO3 ratio (14:300; 17:300; 20:300 gr/ml). The highest yield of PCC was reached from the concentration of nitric acid 2 M and ratio 14 gr : 300 ml which the yield was 84,88%. From the X-Ray Diffraction (XRD) characteristic result, able to know the crystal form that reached was vaterite which was reinforced from analysis result of Scanning Elcetron Microscopy (SEM) with the sphere partical.Key words: Blood cockle shell, carbonation, PCC, SEM, XRD